Kinetic of thermal degradation of alginate-zeolite composites - Milan Kragović; Aleksandra Daković; Marija Marković; Anđela Petković (Zaštita Materijala)
In this work, natural and Fe(III)-modified zeolte were tested as additives for alginate in order to improve its thermal and pyrolytic properties. For that purpose the natural zeolite (NZA) and Fe(III)- modified zeolite coated with alginate (FeA) were used. Thermal degradation of the samples was investigated by using thermal analytic techniques, thermogravimetric (TG) and differential thermal analysis (DTA). The samples were heated from 25oC to 1000ºC at different heating rates (from 5 to 20ºC). From experimental results, thermal degradation of the sodium alginate could be clearly separated into several stages based on the weight loss and the weight loss rate. The kinetic parameters (activation energy and pre-exponential factor) for the main degradation phase (from 180 to 500ºC) thus were estimated by using the pseudo first-order assumption. The results showed that used zeolites affected the thermal properties of the alginate and reduce activation energy required for pyrolysis from 87.30 kJ/mol for pure alginate to 72.75 kJ/mol for NZA and 63.35 kJ/mol for FeA. These pyrolysis investigations can be useful for better understanding the thermal stability of these alginate biocomposites and provide necessary information for thermally processing wastes from these biodegradable materials.